Effect of pre and post emergence herbicides for weed management in bermuda grass (Cynodon dactylon) var. Tif dwarf 419 - SINGH, BABITA; SINDHU, S S; PINDER, ROHIT; YADAV, HARENDRA; NAMITA, NAMITA; DAS, T K (The Indian Journal of Agricultural Sciences, 2018)
Turf grasses are the plants which form a continuous ground cover and is the assurance of a lush, high-quality lawn but the presence of weeds during green establishment can reduce growth and turf quality. Field experiment was conducted to investigate efficacy of Pendimethalin (1.0 kg a.i./ha) – pre emergence, Atrazine (1.0 kg a.i./ha) - pre emergence, Carfentrazone (30 g/ha)- post emergence (40 DAS), Metribuzin (300 g/ha) - pre emergence, Pendimethalin (0.75 kg/ha) + Metribuzin- pre emergence, Pendimethalin (Pre emergence) + Carfentrazone- (Post emergence), Pendimethalin (Pre emergence) + Metribuzin (Post emergence), Atrazine (Pre emergence) + Carfentrazone (Post emergence), Atrazine (Pre emergence) + Metribuzin (Post emergence), manual weeding (four hand weeding) on the establishment of Tif dwarf 419 Bermuda grass from sprigs. The results suggest that application of Pendimethalin @ 0.75 l/ha (pre-emergence) + Carfentrazone @ 0.0225 kg/ha (post-mergence) at 40 days after sowing was effective for controlling the weeds followed by Atrazine @ 0.75 l/ha (pre-emergence) + Carfentrazone @ 0.0225 kg/ha (postemergence) at 40 days after sowing. Carfentrazone (30g/ha) alone as post emergence herbicide recorded about 75% weed mortality.